Hepatocyte-specific S100a8 and S100a9 transgene expression in mice causes Cxcl1 induction and systemic neutrophil enrichment - Wiechert, Lars; Heß, Jochen (Cell communication and signaling, 2012)
Calprotectin consists of the Ca2+-binding proteins S100a8 and S100a9 that are induced in epithelial cells in response to tissue damage and infection. Both proteins are also secreted by activated innate immune cells and numerous studies demonstrate their crucial role in pathological conditions of acute and chronic inflammation.